Constructing a Cost–Benefit Analysis Framework for Digital Twin–Enabled Spatial Planning: Articulating (Hidden) Costs and (Implicit) Benefits in Governmental Organizations - Leewis, Sam; Smit, Koen; van Meerten, John; Buijsse, Ronald (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Digital Twins (DTs) are increasingly used in urban planning and public-sector spatial development to support evidence-based decision-making and scenario analysis. However, many DT initiatives struggle to progress beyond pilot stages (Hiller et al., 2026), partly due to the absence of a clear and validated cost–benefit analysis (CBA) framework. Existing evaluations often underestimate lifecycle costs while failing to adequately articulate indirect and intangible benefits such as improved decision quality, stakeholder engagement, and transparency. This research-in-progress study tries to address this gap by asking how hidden costs and implicit benefits of DTs in public-area development can be identified and structured into a first version of a CBA framework. Using a Design Science approach, we combine a scoping review further supplemented with exploratory expert interviews in a Dutch spatial planning context. Preliminary findings highlight lifecycle and governance-related costs and indicate that DT value primarily emerges through improved decision quality and reduced downstream failure costs, though further detailing and validation is required in future research.